Republic of Djibouti - Pension System Reform : Strategic Note - World Bank (Washington, DC, 2013)
The Government of Djibouti has committed to reform its pension system in order to restore financial sustainability and improve management. To this end, it requested the World Bank to elaborate a pension reform strategy that identifies the major financial and institutional constraints facing the pension funds and explores restructuring options. This policy note summarizes the major diagnosis and policy recommendations of the study, reflecting comments from government officials and the Bank's technical experts during the internal review meeting held on March 15, 2001. In the case of Djibouti, a two-stage reform program is proposed. A first stage would concentrate on consolidating a modest pay-as-you-go system, and involve executing three major activities: 1) implementing institutional reforms to improve governance and management, and to generate efficiency gains that enhance service delivery and reduce administrative costs; 2) addressing short-term financial needs by normalizing government contributions, defining a plan to refinance government arrears, and introducing a ceiling for the replacement rate in the regime for parliamentarians; and 3) improving the medium-term financial situation of the pension funds. A second stage of the reform program would focus on merging the Social Protection Organism (OPS) and the National Pensions Fund (CNR); and introducing/reinforcing incentives to promote contractual savings.